2008
DOI: 10.1007/s00432-007-0332-8
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer occurs earlier in those exposed to tobacco smoke: implications for screening

Abstract: Background-Colorectal cancer (CRC) is the third most common cancer in the USA. While various lifestyle factors have been shown to alter the risk for colorectal cancer, recommendations for the early detection of CRC are based only on age and family history.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 49 publications
(47 reference statements)
0
18
1
Order By: Relevance
“…39,40 Another study found that individuals with heavy, long-term tobacco smoke exposure were significantly younger at the time of colorectal cancer diagnosis compared to lifelong never smokers, and screening for colorectal cancer was suggested 5e10 years earlier for persons with a significant lifetime history of exposure to tobacco smoke. 41 By a cohort study, smoking was associated with an increased risk of colorectal cancer mortality. 42,43 Because the age of colorectal cancer patients is younger in smokers and the mortality rate is also higher in smokers, the colorectal cancer screening strategy should be considered 5e10 years earlier than the average risk population.…”
Section: Cigarette Smoking and Colorectal Cancersmentioning
confidence: 99%
“…39,40 Another study found that individuals with heavy, long-term tobacco smoke exposure were significantly younger at the time of colorectal cancer diagnosis compared to lifelong never smokers, and screening for colorectal cancer was suggested 5e10 years earlier for persons with a significant lifetime history of exposure to tobacco smoke. 41 By a cohort study, smoking was associated with an increased risk of colorectal cancer mortality. 42,43 Because the age of colorectal cancer patients is younger in smokers and the mortality rate is also higher in smokers, the colorectal cancer screening strategy should be considered 5e10 years earlier than the average risk population.…”
Section: Cigarette Smoking and Colorectal Cancersmentioning
confidence: 99%
“…The causal relation between cigarette smoking and colorectal carcinogenesis has been well established recently (19,20). Tobacco-derived nitrosamines and heterocyclic amines are likely causative agents (33)(34)(35)(36)(37)(38)(39). The carcinogens responsible for carcinomas arising in intestinal segments used for urinary conduits are unknown but renal metabolism and urinary excretion of tobacco-derived chemicals is an important route of elimination of these substances.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the studies reviewed previously (Sandler et al 1988;Gerhardsson de Verdier et al, 1992;Mao et.al., 2002), ten new studies have been identified: two cohort (Nishino et al, 2001;Hooker et al, 2008; Table 2.13 available at http://monographs.iarc.fr/ENG/Monographs/ vol100E/100E-02-Table2.13.pdf); seven casecontrol (Sandler et al, 1985a, b;Slattery et al, 2003;Lilla et al, 2006;Wang et al, 2006;Duan et al, 2009;Verla-Tebit et al, 2009; Table 2.14 available at http://monographs.iarc.fr/ENG/ Monographs/vol100E/100E-02-Table2.14.pdf) and one case-only study (Peppone et al, 2008; Four studies investigated risk for cancer or the colon and/or rectum by sex. Sandler et al (1988) reported an increased risk for colorectal cancer in men (RR 3.0; 95%CI: 1.8-5.0) but a protective effect in women (RR 0.7; 95%CI: 0.6-1.0).…”
Section: Cancers Of the Gastrointestinal Tractmentioning
confidence: 99%
“…Hooker et al (2008) When analysing different sources of exposure to second-hand tobacco smoke, Verla-Tebit et al (2009) found no evidence of an increased risk for cancer of the colorectum associated with exposure to second-hand tobacco smoke specifically during childhood or at work, but observed a significant increase in risk associated with spousal exposure. Peppone et al (2008) noted that considerable exposure to second-hand tobacco smoke, especially during childhood, was more likely to lead to an earlier-age diagnosis of cancer of the colorectum.…”
Section: Cancers Of the Gastrointestinal Tractmentioning
confidence: 99%